Sensorineural Hearing Loss and Celiac Disease: A Coincidental Finding. (2009) - Volta, Umberto; Ferri, Gian Gaetano; De Giorgio, Roberto; Fabbri, Angela; Parisi, Claudia; Sciajno, Laura; Castellari, Alessandra; Fiorini, Erica; Piscaglia, Maria; Barbara, Giovanni; Granito, Alessandro; Pirodda, Antonio
Abstract : BACKGROUND: Celiac disease (CD) can be associated with a variety of extraintestinal manifestations, including neurological diseases. A new neurological correlation has been found between CD and sensorineural hearing loss (SNHL). OBJECTIVE: To verify the association between SNHL and CD, and to establish whether the neurological hearing impairment in CD is related to nonorgan-specific and antineuronal antibodies, as well as the presence of autoimmune disorders. METHODS: A sample of 59 consecutive biopsy- and serologically proven CD patients were studied. Among CD patients, 11 were newly diagnosed and 48 were on a gluten-free diet. Hearing function was assessed by audiometric analysis in all CD patients as well as in 59 age- and sex-matched controls. Patients were tested for a panel of immune markers including nonorgan-specific autoantibodies and antineuronal antibodies. RESULTS: SNHL was detected in five CD patients (8.5%) and in two controls (3.4%). In one patient, the SNHL was bilateral, whereas the remaining four had a monolateral impairment. The prevalence of SNHL was not significantly different between CD patients and controls. At least one of the antibodies tested for was positive in two of the five CD patients with SNHL and in 12 of the 54 CD patients without SNHL. Antineuronal antibodies to central nervous system antigens were consistently negative in the five CD patients with SNHL. Only one of the five CD patients with SNHL had Hashimoto thyroiditis. CONCLUSIONS: SNHL and CD occur coincidentally. Hearing function should be assessed only in CD patients with clinical signs of hearing deficiency.